Socio-Economic Adaptation After Natural Disasters In Langaleso Village - Ragil Cahya Ningrum Ragil Cahya Ningrum; Rifai Mardin Rifai Mardin; Dita Septyana Dita Septyana; Deltri Dikwardi Eisenring Deltri Dikwardi Eisenring (Jurnal Peweka Tadulako, 2022)
On September 28, 2018, the earthquake and liquefaction disaster in Langaleso Village, Dolo District, Sigi Regency severely damaged several areas. In addition, other impacts of natural disasters that occur are resulting in changes in the social and economic conditions of the community. This is because the state of their agricultural land was wiped out due to the impact of liquefaction that occurred in Jono Oge village. The damage to the Gumbasa irrigation channel resulted in a decline in the community’s economy. The purpose of this study is to determine the form of adaptation of the Langaleso village community based on social and economic aspects both from before natural disasters, after natural disasters, and current conditions. The research method used is descriptive qualitative data analysis techniques, where data is obtained by observation techniques and interviews conducted in the field. And then, the information that has been received is then processed to get the results of the research objectives. The results of this study are that the community is still trying to adapt to existing needs at present conditions. The main problem that the village community experiences are in the economic sector. The majority of the main work of the community is farmers. Still, with the damage to the irrigation system, the district has not been able to carry out agricultural or plantation activities